Sistem Pendukung Keputusan Pemilihan Kantor Pos Terbaik Menerapkan Metode WASPAS - Herlinda Gulo (Journal of Information System Research (JOSH), 2020)
The development of PT. POS Indonesia, then more branches are open. With more and more branches opening, several problems often arise in each branch, and therefore the leadership of PT. POS Indoesia chooses the best POS Office, with determined alternatives (North Sumatra only). The benefit of selecting the best POS Office is to support the enthusiasm of POS Workers in carrying out their duties. The function of a decision support system in selecting the best POS office by producing an alternative in accordance with predetermined criteria. In this study the authors conducted a case study at the Post Office. Avoiding alleged research on the making of a Post Office election decision support system. The method of decision making in the system that will be designed by the writer uses the WASPAS method to assist in making the selection decision for the best post office selection. The WASPAS method has simple calculations and is easy to understand. The method was chosen because the decision support model in which the main equipment is a functional hierarchy with the main input is human perception, ie in this case the person who is an expert in the problem or the person who understands the problem of choosing the best post office.